PENENTUAN GRADE BIJI KOPI ROBUSTA MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS - Aristoteles Aristoteles; Favorisen R. Lumbanraja; Astria Hijriani; Meria Nensi (Lambung Mangkurat University, 2022)
Coffee beans are one of the raw materials as well as a result of planting by farmers which provides special benefits for the survival of the Indonesian people. Coffee is used as a refreshing drink ingredient and in today's life, coffee drinks have become a lifestyle for millennial people. The type of coffee that is widely cultivated is the robusta coffee bean type, because this robusta coffee is mostly produced in Indonesia, reaching 87.1% of the total coffee production in Indonesia. One of the largest producers of robusta coffee in Indonesia is the Dempo Pagar Alam Mountain Slope Coffee Plantation, South Sumatra. Therefore in this study using the type of robusta coffee beans which grade or quality will be determined according to the applied criteria. This study aims to determine the grade of robusta coffee beans in the Dempo Pagar Alam Mountain Slope Coffee Plantation in South Sumatra using the AHP (Analytical Hierarchy Process) method.The stages in this research are the preparation of research data collection, namely primary and secondary which are stored in a text file (.txt) with tens of data and the second stage is determining criteria and alternatives, compiling a hierarchical structure, compiling a paired comparison matrix, looking for priority vector values and eigen vectors, alternative ranking results, and accuracy testing. The results of this study are expected to provide benefits to see the results of the robusta coffee bean grade ranking in the Slope Coffee Plantation of Mount Dempo Pagar Alam, South Sumatra by using the AHP method. Keywords : Coffe Beans,Grade, AHP (Analytical Hierarchy ProcessBiji kopi merupakan salah satu bahan baku sekaligus sebagai hasil dari penanaman oleh petani yang memberikan manfaat tersendiri bagi kelangsungan hidup masyarakat Indonesia. Kopi dijadikan sebagai bahan minuman penyegar dan di kehidupan sekarang ini minuman kopi telah menjadi gaya hidup bagi masyarakat milenial. Adapun jenis kopi yang banyak dibudidayakan yaitu jenis biji kopi robusta, karena kopi robusta ini paling banyak diproduksi di Indonesia mencapai 87,1% dari total keseluruhan produksi kopi di Indonesia. Salah satu daerah penghasil jenis kopi robusta terbesar di Indonesia yaitu Perkebunan Kopi Lereng Gunung Dempo Pagar Alam Sumatera Selatan. Oleh karena itu dalam penelitian ini menggunakan jenis biji kopi robusta yang akan ditentukan grade atau kualitasnya sesuai dengan kriteria yang diterapkan.Penelitian ini memiliki tujuan untuk menentukan grade biji kopi robusta di Perkebunan Kopi Lereng Gunung Dempo Pagar Alam Sumatera Selatan dengan menggunakan metode AHP (Analytical Hierarchy Process). Tahapan dalam penelitian ini yaitu persiapan pengumpulan data penelitian yaitu primer dan sekunder yang disimpan di dalam file teks (.txt) dengan jumlah data puluhan dan tahap kedua adalah menentukan kriteria dan alternatif, penyusunan struktur hierarki, menyusun matriks perbandingan berpasangan, mencari nilai priority vector dan eigen vector, hasil perangkingan alternatif, dan pengujian akurasi. Hasil penelitian ini diharapkan dapat memberikan manfaat melihat hasil perangkingan grade biji kopi robusta yang ada di Perkebunan Kopi Lereng Gunung Dempo Pagar Alam Sumatera Selatan dengan merepakan metode AHP.Kata Kunci : Biji Kopi, Grade, AHP (Analytical Hierarchy Process)